Regularly Arranged Micropore Architecture Enables Efficient Lithium-Ion Transport in SiOx/Artificial Graphite Composite Electrode - Lim, Jaejin; Kang, Dongyoon; Bak, Cheol; Choi, Seungyeop; Lee, Mingyu; Lee, Hongkyung; Lee, Yong Min (Nano-Micro Letters, 2025)
To enhance the electrochemical performance of lithium-ion battery anodes with higher silicon content, it is essential to engineer their microstructure for better lithium-ion transport and mitigated volume change as well. Herein, we suggest an effective approach to control the micropore structure of silicon oxide (SiOx)/artificial graphite (AG) composite electrodes using a perforated current collector. The electrode features a unique pore structure, where alternating high-porosity domains and low-porosity domains markedly reduce overall electrode resistance, leading to a 20% improvement in rate capability at a 5C-rate discharge condition. Using microstructure-resolved modeling and simulations, we demonstrate that the patterned micropore structure enhances lithium-ion transport, mitigating the electrolyte concentration gradient of lithium-ion. Additionally, perforating current collector with a chemical etching process increases the number of hydrogen bonding sites and enlarges the interface with the SiOx/AG composite electrode, significantly improving adhesion strength. This, in turn, suppresses mechanical degradation and leads to a 50% higher capacity retention. Thus, regularly arranged micropore structure enabled by the perforated current collector successfully improves both rate capability and cycle life in SiOx/AG composite electrodes, providing valuable insights into electrode engineering. Highlights: 1 The internal pores of the electrode were engineered into a regularly arranged micropore (RAM) structure by introducing a perforated and surface-modified Cu current collector (pCu). 2 The pore network, favorable for fast ion transport, effectively mitigates concentration polarization and enables uniform ion distribution, contributing to high-rate operation of lithium-ion batteries. 3 The RAM structure, featuring a unique interlocking electrode configuration and hydroxyl-rich pCu surface, suppressed mechanical degradation and improved long-term cyclability by 50%.